Microbial Pattern and Sensitivity Analysis of Otitis Externa Patients in Makassar, Indonesia - Joy Tobing; Riskiana Djamin; Sutji Pratiwi Rahardjo (Faculty of Medicine, Hasanuddin University., 2022)
Introduction: Globally, the cases of otitis externa were increased, followed by the incidence of antimicrobial resistance. Several factors, such as untrained medical health personnel and unprescribed antibiotics, are thought to play a major role in this phenomenon. This study aims to determine the bacterial patterns and antimicrobial sensitivity in otitis externa patients in Makassar, South Sulawesi, Indonesia. Methods: This cross-sectional study was conducted from November 2020 to February 2021 at Dr. Wahidin Sudirohusodo and Health Laboratory Center, Makassar, South Sulawesi, Indonesia. There were in total 33 subjects with otitis externa participating in this study. The secretion from the outer ear canal was taken and cultured using Mac Conkey agar for bacteriological examination and Vitek 2 for antimicrobial sensitivity. This study assessed age, sex, and type of otitis externa. All data analyses used SPSS version 26.00 (IBM Corp., Armonk, New York). Bacteria patterns and otitis externa were analyzed using the Fisher test. Results: Fourteen cases (42.4%) were caused by Pseudomonas Aeruginosa. Most Gram-negative bacteria were sensitive to ciprofloxacin, gentamicin, amikacin, and meropenem. Staphylococcus haemolyticus, Staphylococcus capitis, and Staphylococcus epidermidis were the most resistant Gram-positive bacteria. Aerobic bacteria in otitis externa were sensitive to antimicrobials (p<0.023). Conclusion: Gram-negative aerobic bacteria were common causes of otitis externa, with Pseudomonas aeruginosa being the most common isolated bacteria. Ciprofloxacin, gentamicin, amikacin, and meropenem were sensitive antimicrobials for otitis externa.